(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Health promotion (HP) in grassroots sports often depends on the commitment and leadership of sports club management (SCM) that serves on the front-line to implement HP initiatives. However, management often lacks the knowledge, support, and tools to integrate HP activities. This study aims to create a theoretical and practical implementation guide for SCM based on the health promoting sports club (HPSC) framework. The research addresses the need for practical tools and tailored guidance for sports club (SC) governance, offering an innovative, settings-based framework to sustainably implement HP initiatives. Methods: This guide is being developed through mixed-methods, combining three components: (1) five data collection meetings with international researchers to develop the theoretical content and background; (2) practice-based case studies, to describe real-life interventions; and (3) development of an HP observational tool through four steps: literature review, three-round Delphi study, pilot testing, and test–retest validation. Results: Twenty-two international researchers are contributing to develop sections of the guide: (1) the theoretical content and background, including: (a) contextualisation of the settings-based approach providing a five-stages development model guiding management from a passive to comprehensive HPSC, (b) defining the ‘health-promoting sports manager’ as “a manager who actively integrates HP into club policies, structure, and daily practices”, (c) refining 49 strategies from the management level of the HPSC framework into actionable items, and (d) streamlining the HPSC logic model to support managers with understanding mechanisms of change to become an HPSC; (2) SC case studies from SCM who have implemented successful HP initiatives, and (3) co-developing a validated observational tool to assess the HP environment in SCs based on four health determinants (economic, environmental, organisational, and social) from the HPSC model. Conclusion: This study introduces a comprehensive implementation guide designed to assist SCM to systematically integrate HP across club structures and practices. The guide seeks to support and empower SCM to enhance the health, wellbeing, athletic performance, and engagement of club members and the wider community. Support/Funding Source: This work was conducted within the ‘Promoting Physical Activity and Health in Sports Clubs’ WHO HEPA Working Group. No external funding was received beyond institutional support.